A simplified procedure for estimating nonlinear seismic demand of tall piers. (1st November 2018) - Chen, Xu; Guan, Zhongguo; Spencer, Billie F.; Li, Jianzhong
Highlights: Propose a simplified procedure estimating nonlinear seismic response of tall piers. Investigate the contribution of each vibration mode to seismic response. The proposed procedure could estimate seismic response with satisfying accuracy. Abstract: More than 40% of the bridges in mountainous areas of Southwest China are constructed with piers having a height of over 40 m. The seismic response of such tall pier structures is usually estimated by nonlinear response history analysis and/or adaptive pushover procedures; while providing satisfactory results, these methods can be quite time consuming and computational demanding. Therefore, this paper proposes a simplified procedure for estimating the nonlinear seismic response of tall piers. The influence of plastic deformation at the base on dynamic properties (natural periods and mode shapes) of a linearized system for the tall piers is first investigated, using a numerical model of the prototype bridge, based on an equivalent linearization technique. Using these results, a simplified procedure is proposed to predict the distribution of seismic shear force and bending moment along the pier height, as well as the curvature ductility ratio at the pier base. The efficiency of the proposed procedure is verified with numerical examples of tall piers subjected to recorded ground motions, through comparing the seismic demands determined by this method with rigorous nonlinear response history analysis. The results show that the proposed method can efficiently estimate the distribution of both shear force and bending moment along the height of the tall pier; the curvature ductility ratio at pier base can be predicted with errors around 10%.